Employees' perception toward on-site childcare centres to working parents / Farah Fatini Zainal Abidin and Raja Nur Syakirin Raja Ibrahim - Zainal Abidin, Farah Fatini; Raja Ibrahim, Raja Nur Syakirin (2018)
This chapter is divided into several sections. It starts with Section 1.1 that touched on the chapter review. Section 1.2 is regarding the background of the study. It is being continued with Section 1.3 that is discussing research objectives. In addition, Section 1.4 focusing on research questions. Besides, Section 1.5 is regarding the hypotheses while Section 1.6 is concerned with the heart of the research which is problem statement. In Section 1.7, is the significance of study while the Section 1.8 scope of research. Section 1.9 focused on the definition of terms. Lastly is Section 1.10 which is highlighting the organization of research. This research is relating to the employees’ perceptions toward on-site childcare to working parents and it is being conducted in the higher institution, Universiti Teknologi MARA that involves two campuses which are UiTM Tapah, Perak and UiTM Raub, Pahang